Online diet planning system - Farah, Abdullah (2011)
Most people are concern about what they eat everyday. This is because "we are what we eat".People tend to search information about the things that they eat or what related to their diet.Nowadays,there are systems which help people to manage their diet.However,the systems are not specifically focusing on the user's own needs.Different people will require different dietary needs or nutrition for their body.This is due to variety of weight, daily activity level and so on.So they need something that will help them with their own personal body needs.The system that has been developed is an Online Diet Planning System.This web-based application system will help user to get information about their dietary intake.There will be dietary recommendations for the user based on what they need.It is more focusing on the user with his or her own needs rather than just giving the general recommendations to all users.Moreover,this system is focuses on users in Malaysia.